Quintus of Smyrna's Posthomerica, A study of heroic characterization and heroism. - Tine Scheijnen (Mnemosyne, Supplements, 2018)
Quintus of Smyrna's Posthomerica (3rd century C.E.) is of great literary value to the field of Greek epic. It is a stylistic imitation of Homer and recounts what Iliad and Odyssey have left untold of the Trojan War. Tine Scheijnen offers the first linear study of this still little-known poem. Progressing from book 1 to 14, she focusses on key issues such as Homeric similes and characterization of heroes (especially Achilles and his son Neoptolemus). Ideologically, Quintus engages in a critical way with Homer, but possibly also Vergil, Triphiodorus and tragedy. Scheijnen's work can be read as a thorough introduction to Quintus' Posthomerica , while also offering new insights into Homer reception, the conception of heroes and heroism in Greek epic.